2021
DOI: 10.1021/acs.iecr.0c04683
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation of Segregation for Nonspherical Particles in a Fluidized Bed Solids Mixer

Abstract: A binary mixture of particles varying in size, shape, or density tends to segregate in many different flow situations. Removal of segregation is an important goal as it is often detrimental to process efficiency and product quality. The focus of the current work is to see the effect of the shape of particles on segregation in the particular case of a fluidized bed solids' mixer. The present work describes an experimental method to study the evolution of segregation and its dependence on both the shape and size… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 46 publications
(49 reference statements)
5
13
0
Order By: Relevance
“…It is observed that fine prolate particles show the best mixing. This trend agrees with previous studies in a fluidized bed and vertical vibrated bed. , …”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…It is observed that fine prolate particles show the best mixing. This trend agrees with previous studies in a fluidized bed and vertical vibrated bed. , …”
Section: Resultssupporting
confidence: 93%
“…In comparison to oblate particles, prolate particles demonstrate better mixing. This resulting trend for the nonspherical particle has also been observed by Verma et al 34 in a fluidized bed and agrees with this study.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…This mixture that arrives later is rich in large particles owing to their lower acceleration. A similar trend in segregation is observed due to the particle size ratio differences in other systems, such as a fluidized bed solid-mixer, vibrated packed solid-mixer, and horizontal rotating cylinder. …”
Section: Resultssupporting
confidence: 62%